The Haunted Mask II - "Stine, R.L" (Scholastic: London, 1995)
After last year's terrifying Halloween, Carly Beth buried her old haunted mask. Now her friend Steve wants to find a mask just as scary, but she refuese to tell him where she bought hers. At the last minute, Steve encounters a stranger wearing Carly Beth's old mask, and the stranger leads him to a boarded-up novelty shop. Steve steals a creepy mask he finds in the basement. What he doesn't realize is that Carly Beth's mask is alive and using him to get her back
Keywords: Horror films